Analisis Kebutuhan Model Bimbingan Klasikal dengan Media Genre Kit untuk Pemahaman Resiko Seksual Pranikah - Mahfudzoh, Durotun; Hartinah, Sitti; Muljani, Sutji (Jurnal Simki Pedagogia, 2025)
This study aims to explore the need for the implementation of a classical guidance model that utilizes Genre Kit media in improving students' understanding of premarital sexual risks. This study uses the Research and Development method consisting of needs analysis, model design, trials, and evaluation. Data collection was carried out through interviews, observations, and surveys involving a sample population of 40 students and 3 counselors. The analysis techniques applied include descriptive analysis to describe the findings and inferential analysis to identify differences between groups that were given intervention and those that were not given intervention. The research findings show that the implementation of Genre Kit media in classical guidance can significantly improve students' understanding of premarital sexual risks. Based on these results, this study concludes that the guidance model developed can be an effective and attractive alternative to increase students' awareness of sexual risks.